2002
DOI: 10.4049/jimmunol.169.11.6236
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Regulates the Expression of the Human Complement Receptor 2 Gene

Abstract: CR2 is a key regulator of the B cell response to Ag. Here we show that NF-κB enhances the expression of the human CR2 gene. Promoter truncation, deletion, and mutagenesis studies indicated a functional role for a consensus NF-κB promoter element, as well as a heterogeneous nuclear ribonucleoprotein D element and an overlapping X box/E box. By supershift analysis, the first two elements bound NF-κB p50 and p65 and heterogeneous nuclear ribonucleoprotein RNP D, respectively. The X box/E box bound regulatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…3, C and D, the representative results from the experiments repeated four times showed that the 1.8-kb CML66-L promoter in the sense orientation had strong promoter activities compared with the antisense-oriented CML66-L promoter control and the no-insert vector control in both Hela cells and HCCT cells (not shown). The strength of sense-oriented CML66-L promoter was in a level equivalent to that of SV40 promoter in pGL-3 Control vector (the positive control, not shown) (22,23). In contrast, CML66-S promoter in the sense orientation had much low promoter activities in comparison to that of CML66-L promoter in Hela cells and HCCT cells.…”
Section: Predominant Expression Of Cml66-l In Tumor Cells Resulted Frmentioning
confidence: 96%
“…3, C and D, the representative results from the experiments repeated four times showed that the 1.8-kb CML66-L promoter in the sense orientation had strong promoter activities compared with the antisense-oriented CML66-L promoter control and the no-insert vector control in both Hela cells and HCCT cells (not shown). The strength of sense-oriented CML66-L promoter was in a level equivalent to that of SV40 promoter in pGL-3 Control vector (the positive control, not shown) (22,23). In contrast, CML66-S promoter in the sense orientation had much low promoter activities in comparison to that of CML66-L promoter in Hela cells and HCCT cells.…”
Section: Predominant Expression Of Cml66-l In Tumor Cells Resulted Frmentioning
confidence: 96%
“…The human CR2 gene (OMIM 120650) encodes a membrane glycoprotein, consisting of 15 repeating structures termed short consensus repeats (SCRs), that is expressed on mature B cells and follicular dendritic cells, as well as an alternatively spliced 16 SCR variant that is expressed primarily on follicular dendritic cells (13). Its relative expression is primarily controlled at the level of transcription by the proximal promoter (14)(15)(16)(17), and cell and lineage specificity of expression is regulated by an intronic silencer (18,19). CR2 binds C3 degradation products covalently bound to antigen in the process of complement activation, as well as EBV (20), the immunomodulatory protein CD23 (21), and IFN-␣ (22).…”
mentioning
confidence: 99%
“…Both genes have been found to be controlled, via reporter assays, by two distinct regions of the gene: the proximal promoter regions and sequences within the first intron. The human CD21 gene has been shown to possess a number of functional sites, including Sp1, AP1, AP2, and E box sites proximal to the TATA box sequence, and NF-B and heterogeneous ribonucleoprotein sites further upstream (Ϫ531 and Ϫ495 relative to the transcription induction site, respectively) (13)(14)(15)(16)(17)(18)(19). The mouse CD21 promoter possesses a functional Oct-1 site (equal binding via EMSA with T and B cell nuclear extracts), a consensus Pax5 binding site (showing a B cell-specific EMSA pattern), and a conserved NF-B site (also showing equal binding via EMSA with T and B cell nuclear extracts) all within the first 280 bp of the promoter region (7, 20 -22).…”
mentioning
confidence: 99%